CH4-C3H8 mixed gas hydrates formation in marine mud and foraminifera-rich sand from the South China Sea: an experimental approach - Mao, Peixiao; Schicks, Judith M.; Pan, Mengdi; Wu, Nengyou (Frontiers in Marine Science, 2025)
CH4-C3H8 mixed gas hydrates are widely distributed in deep-sea weakly-consolidated muddy sediments of the South China Sea, enriched with biological clastics like foraminifera-rich sand. However, the role of complex mineral composition of mud and foraminifera-rich sand on the formation of these natural gas hydrates remains unclear. This study employed five natural sediments from the South China Sea, i.e., foraminifera-rich sand, a mixture of mud and foraminifera-rich sand, and three different mud samples, to reveal their effects on CH4-C3H8 mixed gas hydrate formation. Gas hydrates were formed from water and a constant-feed gas composition containing 96 mol% CH4 and 4 mol% C3H8. The formation process was continuously observed using microscopic observation and in situ Raman spectroscopy. Additional ex situ Raman measurements were also conducted jointly. The results show that only structure II gas hydrates were formed with two crystal morphologies in these sediments, showing no significant differences in gas composition or large-to-small cavity ratio. The concentration of CH4 and C3H8 in the mixed gas hydrates almost did not vary over time in clean foraminifera-rich sand or mud. In a mixture of mud and foraminifera-rich sand, CH4 was preferentially encased into the hydrate cavities at the initial formation stage, while the encasement of C3H8 increased during the ongoing formation process. Not all small 512 cages and large 51264 cages were filled with CH4 during the euhedral hydrate crystals formation. Foraminifera-rich sand, large quartz particles, illite, and kaolinite positively influence the encasement of CH4 into hydrate cavities. These findings provide insights into how marine sediment composition influences gas hydrate formation and their implications for marine ecosystem functioning and structure.